Healthcare utilization and expenditures among adults with type 2 diabetes mellitus and comorbid psychological distress - Qu, Wenjie; Wang, Ying; Zhong, Yaqin; Cao, Xin; Wang, Yuting; Chen, Rongrong; Zhao, Miaomiao; Yang, Weiping; Gao, Yuexia (Frontiers in Endocrinology, 2026)
BackgroundDepressive symptoms and diabetes distress are associated with adverse outcomes in adults with type 2 diabetes mellitus (T2DM). However, no prior studies evaluated the association between healthcare expenditures, utilization, and psychological health in adults with T2DM in rural areas of China. The aim of this study was to explore the association between psychological health—specifically depressive symptoms and diabetes distress—and healthcare utilization and expenditures in this population.MethodsThis cross-sectional study was conducted in 15 rural health clinics in Jiangsu Province, China, and involved 843 adults with T2DM. Psychological health was assessed using the 17-item Diabetes Distress Scale (DDS-17) and the 10-item Center for Epidemiologic Studies Depression Scale (CESD-10). Healthcare utilization and expenditures were evaluated with negative binomial, logistic, and ordinary least squares (OLS) regression models.ResultsOf 843 participants, a total of 32.62% of the sample were comorbid with distress, depression, or both. Each 1-point increase in diabetes distress score was associated with a 44% increase in the expected number of annual outpatient visits (IRR = 1.44, P<0.05), a 52% increase in the odds of inpatient service utilization (OR = 1.52, P <0.05), and a 43.3% increase in outpatient costs (eβ-1 = 0.433, P<0.05). For each point increase in depressive symptom score, the expected number of annual outpatient visits increased by 4% (IRR = 1.04, P<0.01), the odds of inpatient service utilization increased by 4% (OR = 1.04, P <0.01), and total medical expenditures increased by 2% (eβ-1 = 0.02, P<0.05).ConclusionOur study observed that Diabetes distress is associated with higher outpatient costs, while diabetes with depressive symptoms is associated with higher total medical expenditures. These findings suggest that psychological screening and care interventions for adults with diabetes may be essential.